2019
DOI: 10.1002/syst.201900021
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Formation and Annealing of Colloidal Crystals Induced by Light‐Powered Oscillations of Active Particles

Abstract: Self‐organization through communication is observed in many systems throughout nature, often resulting in a collective response to a change in the environment. Herein, we demonstrate a synthetic system that exhibits chemical communication between small active and larger inactive particles which drives the reversible assembly of the latter into colloidal crystals. Specifically, we report the autonomous hexagonal packing of inert silica particles due to the oscillatory behavior of neighboring silver phosphate mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…However, this is not required for a swarming wave, because colloidal particles are in this case merely flow tracers. Swarming waves have been observed with pure Ag or Ag 3 PO 4 microparticles and nanoparticles (21,24,25,50) (see movie S11 for a demonstration from our own laboratory). We have even seen it on glass slides coated with Ag (fig.…”
Section: Necessary Ingredients For Colloidal Waves To Occurmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this is not required for a swarming wave, because colloidal particles are in this case merely flow tracers. Swarming waves have been observed with pure Ag or Ag 3 PO 4 microparticles and nanoparticles (21,24,25,50) (see movie S11 for a demonstration from our own laboratory). We have even seen it on glass slides coated with Ag (fig.…”
Section: Necessary Ingredients For Colloidal Waves To Occurmentioning
confidence: 99%
“…The recent discoveries of photochemically active, oscillating silver-containing colloids (21)(22)(23)(24)(25) have ushered in a new member to this exciting family of nonlinear processes. An inert polymer microsphere half-coated with silver (an "active colloid"; Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Although an earlier study by us has shown that, 57 under continuous illumination, tracer particles were periodically repelled and attracted from a Ag Janus oscillating motors, regular crystals were never observed, unlike the case with oscillating Ag 3 PO 4 microparticles. 59 However, upon intermittent illumination at 5 Hz, negatively charged SiO 2 microspheres rapidly migrated and assembled around clusters of Ag Janus particles that were stuck on the substrate, forming crystalline clusters within seconds. A closer look reveals that SiO 2 microspheres were attracted more strongly than being repelled as light was turned off and on, respectively, thus achieving a net migration over time.…”
Section: Resultsmentioning
confidence: 99%
“…Plasmonic active matter uses light to power the locomotion and/or self-assembly in various applications. [13][14][15][16] Alternatively, plasmonic enhancement has been used as a sensing mechanism within MOFs where there are metal particles impregnating the MOF or the MOF is grown around metal nano particles. [17][18][19] These techniques require an independent metal particle to be associated with the MOF, and does not provide locomotion to the particle.…”
Section: Introductionmentioning
confidence: 99%